Analisis parameter kinetika neutron reaktor NuScale dengan selongsong Ti3SiC2 menggunakan metode Monte Carlo - Fajar Arianto; Wahyu Budi Utomo; Rahmania Serli Assifa; Indras Marhaendrajaya (Jurnal Teras Fisika: Teori, Modeling, dan Aplikasi Fisika, 2026)
Fuel cladding is a critical component in nuclear reactor safety. Accident Tolerant Fuel (ATF) is developed to enhance fuel resilience, including the use of Ti3SiC2 MAX phase material. This study analyzes neutron kinetic parameters, specifically the effective delayed neutron fraction (βeff) and mean neutron generation time (Λ), in the NuScale reactor using Monte Carlo N-Particle 6.2 (MCNP6.2). Simulation results indicate that Ti3SiC2 exhibits a disadvantage with a sharper decline in βeff compared to M5, despite a slightly higher initial value (0.0073) than M5 (0.0069). Furthermore, Ti3SiC2 is less superior due to its smaller Λ leading to faster power responses. Nevertheless, both materials remain within thermal reactor safety limits throughout the 5-year operational period.